2010
DOI: 10.1093/nar/gkq037
|View full text |Cite
|
Sign up to set email alerts
|

Modifications in host cell cytoskeleton structure and function mediated by intracellular HIV-1 Tat protein are greatly dependent on the second coding exon

Abstract: The human immunodeficiency virus type 1 (HIV-1) regulator Tat is essential for viral replication because it achieves complete elongation of viral transcripts. Tat can be released to the extracellular space and taken up by adjacent cells, exerting profound cytoskeleton rearrangements that lead to apoptosis. In contrast, intracellular Tat has been described as protector from apoptosis. Tat gene is composed by two coding exons that yield a protein of 101 amino acids (aa). First exon (1–72aa) is sufficient for vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
85
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(90 citation statements)
references
References 121 publications
5
85
0
Order By: Relevance
“…9G). These data suggested that both Gag alone and Gag with accessory proteins could activate F-actin polymerization in T cells, as suggested in previous studies (44,45,66). Altogether, our data showed that Gag expression in Jurkat T cells activated Rac1 and increased the intracellular F-actin content.…”
Section: Rac1 Knockdown Modulates Hiv-1 Gag Vlp Release and Gag Intrasupporting
confidence: 90%
See 3 more Smart Citations
“…9G). These data suggested that both Gag alone and Gag with accessory proteins could activate F-actin polymerization in T cells, as suggested in previous studies (44,45,66). Altogether, our data showed that Gag expression in Jurkat T cells activated Rac1 and increased the intracellular F-actin content.…”
Section: Rac1 Knockdown Modulates Hiv-1 Gag Vlp Release and Gag Intrasupporting
confidence: 90%
“…The literature has reported an effect of the HIV-1 Tat and Nef accessory proteins on several Rac1-derived signaling pathways (44,45,66). We thus decided to study if the effect of the Rac1-Wave2-IRSp53-Arp3 signaling pathway on virus production observed here was mediated by HIV-1 accessory proteins or solely by the Gag viral protein.…”
Section: Rac1 Knockdown Modulates Hiv-1 Gag Vlp Release and Gag Intramentioning
confidence: 90%
See 2 more Smart Citations
“…DNA Affinity Immunoblotting Assay-The DNA affinity immunoblotting assay was performed as described previously (6) with minor modifications (42). Briefly, 100 g of nuclear protein extracts from Jurkat cells were incubated at 4°C for 30 min with 25 nM concentrations of a 5Ј-labeled biotin probe that contains the double B consensus motif located in the HIV-1 LTR promoter (5Ј-AGCTTACAAGGGACTTTCCGCTGGG-GACTTTCCAGGGA-3Ј) or with a probe that contains the estrogen receptor DNA element, a non-related NF-B gene (43).…”
Section: Methodsmentioning
confidence: 99%